1996
DOI: 10.1038/bjc.1996.603
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of asymptomatic gastric cancer

Abstract: Summary The clinicopathological profiles of 419 patients with asymptomatic gastric cancer (AGC) first detected by gastric screening, were reviewed and compared with those of the 1727 patients with symptomatic gastric cancer (SGC). The incidence of AGC increased gradually and has amounted to 30% of the total resected cases in recent years. About 75% of AGC cases were of early cancer and 84% were negative for lymph node metastases. In contrast, only 33% of SGC cases were of early cancer and 57% were node positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…The early detection of these tumors is an important issue for further studies. In general, previous reports have shown that patients diagnosed with asymptomatic gastric cancer had a better clinical outcome than those diagnosed with symptomatic cancer [5,15]. The ultimate goal of gastric endoscopic screening is to detect these asymptomatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The early detection of these tumors is an important issue for further studies. In general, previous reports have shown that patients diagnosed with asymptomatic gastric cancer had a better clinical outcome than those diagnosed with symptomatic cancer [5,15]. The ultimate goal of gastric endoscopic screening is to detect these asymptomatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, univariate analysis showed that the proportion of men was higher in the asymptomatic group than the symptomatic group. The reason for this discrepancy may be due to the fact that men have greater accessibility to health checkups (including mass screening or private health assessment clinics) at the workplace than women in Japan [17,24,26]. The proportion of EGC cases among those of gastric cancer is more than 50% in Japan [8], whereas in the West the proportion is much lower [43].…”
Section: Discussionmentioning
confidence: 99%
“…Screening programs for gastric cancer have improved the detection of asymptomatic early gastric cancer, the rate of curative resection, and the chance of long-term survival 12) . The transition of features of gastric cancer further highlight the importance of the postoperative QOL, as well as reducing weight loss and other complications.…”
Section: Discussionmentioning
confidence: 99%